Education on tobacco use interventions for undergraduate dental students. Issue 3 (August 2015) - Hanioka, Takashi; Ojima, Miki; Kawaguchi, Yoko; Hirata, Yukio; Ogawa, Hiroshi; Hinode, Daisuke; Hanada, Nobuhiro; Inoshita, Eiji
Summary: Inadequate training for dental professionals hampers the implementation of tobacco use interventions for the improvement of dental practice and oral and overall health. To improve dental education regarding tobacco use prevention and cessation (DENTUPAC), we examined literature addressing previous efforts and experiences with this goal. The majority of studies, published in the US and Europe, reported that a transition from didactic to clinical education achieved moderate-level interventions. The need for a comprehensive multidisciplinary approach and the low confidence of faculty members in their own ability to effectively teach DENTUPAC are commonly reported barriers to DENTUPAC in clinical settings. Objective structured clinical examinations of standardized patients and motivational interviewing have proven consistently successful in DENTUPAC and are included in faculty development workshops and internet-based training. However, levels of intervention from dentists on quitting smoking reported by their patients were relatively low compared to those from physicians, although most dentists reported that they counsel patients. In addition to previous efforts and experiences in developing and disseminating DENTUPAC, the optimization of DENTUPAC by evaluating education on health behavior interventions may help increase the involvement of dentists in cessation counseling upon graduation.